Relative contribution of vertical, within-farm and between-farm transmission of Mycoplasma synoviae in layer pullet flocks. Issue 1 (2nd January 2020) - ter Veen, C.; de Wit, J. J.; Feberwee, A.
ABSTRACT: In this study, the relative contribution of vertical transmission, within-farm transmission and between-farm transmission of Mycoplasma synoviae in layer pullet flocks was quantified using logistic regression analysis. Data from 311 Dutch pullet flocks, of which 172 (55%) were positive for M. synoviae, were included in the study. Also the M. synoviae status of the parent stock of these flocks was included. The M. synoviae status was determined with the M. synoviae rapid plate agglutination test. Data analysis showed that vertical transmission was the most important transmission route for M. synoviae in layers as is demonstrated by an odds ratio of 5.8 ( P = 0.000). A positive association with M. synoviae infections was found for layer pullet flocks on a multi-house farm where at least one other flock was M. synoviae -positive compared to single-house farms (odds ratio 3.1, P = 0.022), while a negative association was found when no other M. synoviae -positive flocks were present (odds ratio = 0.2, P = 0.003). No association was found between M. synoviae status of pullet flocks and poultry farm density. Odds ratios were 0.54 ( P = 0.288) and 0.34 ( P = 0.073), respectively, for medium and highest poultry farm density compared to lowest poultry farm density. This is the first time that the relative contribution of horizontal and vertical transmission of M. synoviae has been quantified. These results can be extrapolated to M. synoviae control in general, and emphasize the importance of M. synoviae control in parent stock and practical channelling.